2021
DOI: 10.36713/epra6970
|View full text |Cite
|
Sign up to set email alerts
|

Binge Watching and Clinical Depression- One Harbinger for Another?

Abstract: Television is one of our most preferred forms of entertainment. Due to the emergence of smartphones and online streaming platforms television is now in our hands and pockets constantly. Depression may be positively related to television viewing affinity. Individuals higher in depression were more likely to binge- watch television shows out of comfort seeking. It also seemed possible that individuals who had higher in depression lack the motivation or cognitive energy to resist the auto- play functions of stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Another major drawback of binging is the risk of goal conflict, resulting in the viewers feeling guilt and shame for having missed their time (Granow et al, 2018;Riddle et al, 2017). Halder et al (2021) observed that viewers binge more often to forget the stress in their everyday lives, and they did find correlations between binging and depression though they could not establish whether depressed people tend to bingewatch more or that binge-watching leads to depression. However, there is some other research suggesting the complete opposite.…”
Section: Impact Of Binge-watchingmentioning
confidence: 94%
“…Another major drawback of binging is the risk of goal conflict, resulting in the viewers feeling guilt and shame for having missed their time (Granow et al, 2018;Riddle et al, 2017). Halder et al (2021) observed that viewers binge more often to forget the stress in their everyday lives, and they did find correlations between binging and depression though they could not establish whether depressed people tend to bingewatch more or that binge-watching leads to depression. However, there is some other research suggesting the complete opposite.…”
Section: Impact Of Binge-watchingmentioning
confidence: 94%